2012
DOI: 10.1051/0004-6361/201220234
|View full text |Cite
|
Sign up to set email alerts
|

On the periodicity of oscillatory reconnection

Abstract: Context. Oscillatory reconnection is a time-dependent magnetic reconnection mechanism that naturally produces periodic outputs from aperiodic drivers. Aims. This paper aims to quantify and measure the periodic nature of oscillatory reconnection for the first time. Methods. We solve the compressible, resistive, nonlinear magnetohydrodynamics (MHD) equations using 2.5D numerical simulations. Results. We identify two distinct periodic regimes: the impulsive and stationary phases. In the impulsive phase, we find t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 67 publications
5
49
2
Order By: Relevance
“…The oscillatory reconnection is initiated in a self-consistent manner instead of driven manner. In a further study of McLaughlin et al (2012), two distinct periodic phases in the oscillatory oscillation were identified for the first time, i.e., the transient, impulsive phase, and the stationary phase. During the observations of solar flares, very short period radio pulsations were found in many studies (e.g., Kliem et al 2000;Tan et al 2007; also the review by Nakariakov & Melnikov 2009).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The oscillatory reconnection is initiated in a self-consistent manner instead of driven manner. In a further study of McLaughlin et al (2012), two distinct periodic phases in the oscillatory oscillation were identified for the first time, i.e., the transient, impulsive phase, and the stationary phase. During the observations of solar flares, very short period radio pulsations were found in many studies (e.g., Kliem et al 2000;Tan et al 2007; also the review by Nakariakov & Melnikov 2009).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This was later also studied by in a similar setting, where they performed a parametric study. McLaughlin, Thurgood, and MacTaggart (2012) reported that the period of the oscillatory reconnection depends on the amplitude of the exciting wave, indicating that the waves are essentially non-linear. Pucci, Onofri, and Malara (2014) perturbed an X-point with magnetosonic perturbations, and also found oscillatory reconnection.…”
Section: Periods Generated By the Flarementioning
confidence: 99%
“…The mechanism giving rise to QPP is not fully understood at present. One possibility pointed out by McLaughlin et al (2012) is that of oscillatory reconnection. The behaviour of oscillatory reconnection is similar to a damped harmonic oscillator and may play a role in generating QPP.…”
Section: Introductionmentioning
confidence: 99%